Orientalism, Postmodernism and Globalization by Brian Turner: Analytical Approach - Amani Abou Rahmah (Studi Multidisipliner: Jurnal Kajian Keislaman, 2023)
In this encyclopedic book entitled (Orientalism, Postmodernism, and Globalism), Brian Turner, the British Marxist philosopher, thinker, and sociologist, discusses the thoughts of prominent intellectuals of modernity and postmodernity, and, most famous orientalists in the history of Orientalism. Turner refutes their opinions regarding the role of religion in societies, and the ability of Islam to be a lever for modernization. After the collapse of Communism and the overwhelming of Western societies in endless social and economic problems, Islam may be the only alternative to Western capitalist hegemony in today's world. Globalization and postmodernism further complicate the notion of “society” and thus challenged the legitimacy and coherence of “sociology” itself, but also they have affected all fields, including Orientalism. Orientalism, under the pluralism of globalization and the violation of all boundaries by postmodernism, seemed an outdated and invalid critical maneuver, not to mention its intrinsic problems.Therefore, Turner wants to take us to a global sociology, through the efforts of social scientists and thinkers who are well aware of the threats, but also the new opportunities posed by postmodernism. Turner singles out special treatment of the postmodern consumer society. He believes that daily life has become part of a global system of commodity exchange and is not easily affected by political leaders, intellectuals, or religious leaders. Therefore, the danger to faith will be in terms of consumerism and its symbols, not in terms of logical arguments and rational research into presuppositions about the West or the East.Brian Turner's ability to bring together such discussions of religion, politics, culture, and intellectuals represents a remarkable integration of cultural analysis into cultural studies. This study aims to provide a critical analysis of Turner's views on the three topics under discussion in the book: Orientalism, globalization, and postmodernism.